A new leaf-tailed gecko of the Uroplatus ebenaui group (Squamata: Gekkonidae) from Madagascar's central eastern rainforests - Ratsoavina, Fanomezana Mihaja; Ranjanaharisoa, Fiadanantsoa Andrianja; Glaw, Frank; Raselimanana, Achille P.; Miralles, Aurélien; Vences, Miguel (Zootaxa, 2015)
We describe a new leaf-tailed gecko species of the Uroplatus ebenaui group from the eastern central rainforests of Madagascar, which had previously been considered as a confirmed candidate species. Our description of Uroplatus fiera sp. nov. relies on integrating evidence from molecular and morphological characters and is based on newly collected material from two localities. A phylogenetic analysis based on multiple mitochondrial DNA fragments places the new species as sister to a lineage of uncertain status (Uroplatus ebenaui [Ca8]), and the clade consisting of these two lineages is sister to a further undescribed candidate species (U. ebenaui [Ca1]). This entire clade is sister to U. phantasticus plus another candidate species. The new species differs from these close relatives, and all other congenerics, by strong differences in DNA sequences of mitochondrial genes (>8.5% uncorrected p-distance in 16S rDNA to all nominal species of the genus) and lacks shared alleles with any of the nominal species in the nuclear CMOS gene. From its closest relatives the new species further differs in its much smaller tail size (relative to U. phantasticus), and a narrower tail, fewer supralabials, and more toe lamellae (relative to U. ebenaui [Ca1]). Morphologically the new species is most similar to U. ebenaui but differs in its larger body size and unpigmented oral mucosa. Given its distribution in central eastern Madagascar, with records from near Fierenana and Ambatovy, its range overlaps with that of U. phantasticus. Based on examination of the U. phantasticus holotype, we confirm that this latter has a blackish pigmented oral mucosa as do those specimens typically attributed to this nomen, thereby confirming its distinctness from U. fiera sp. nov., in which the mucosa is unpigmented.